Gambaran Tingkat Pengetahuan Dan Sikap Keluarga Tentang Perawatan Pasien Resiko Perilaku Kekerasan Di Rumah - Sasmaida - Saragih; Jumaini - -; Ganis - Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this study to is identify the level of knowledge and attitudes about patient care family risk of violent behavior in the home. The design of the research was description, this research was conducted at room Psychiatric Intensive Care Unit (UPIP) Handsome Provincial Mental Hospital, with sample as 33 respondents. The sampling method was accidental sampling. Measuring instrument used was a questionnaire that had been tested for validity and reliability. The research uses Univariate analysis. Based on the results of research conducted, lack of knowledge of the data obtained by 15 respondents (45.5%), insufficient knowledge by 9 respondents (27.3%) and good knowledge of as many as nine respondents (27.3%). Respondents' attitudes about the care of family members with negative violent behavior at home as many as 21 respondents (63.6%) and a positive attitude as many as 12 people (36.4%). The results of this study recommend the hospital conduct health education for families to optimize the knowledge and attitude of the family in the treatment of patients for the risk of violent behavior in the home. Keywords: knowledge, violent behavior, attitudes Reference: 35 (2002-2013)